Clinical Features and Prognosis in Patients with Atrial Fibrillation and Prior Stroke: Comparing the Fushimi and Darlington AF Registries - Hisashi Ogawa; Keitaro Senoo; Yoshimori An; Alena Shantsila; Eduard Shantsila; Deirdre A. Lane; Andreas Wolff; Masaharu Akao; Gregory Y.H. Lip (EBioMedicine, 2017)
Background: Ethnic differences in clinical characteristics, stroke risk profiles and outcomes among atrial fibrillation (AF) patients may exist. We therefore compared AF patients with previous stroke from Japan and the United Kingdom (UK). Methods: We compared clinical characteristics, stroke risk and outcomes among AF patients from the Fushimi AF registry who had experienced a previous stroke (Japan; n = 688; 19.7%) and the Darlington AF registry (UK; n = 428; 19.0%). Results: AF patients with previous stroke in Fushimi were significantly younger (76.8 and 79.6 years of age in Fushimi and Darlington; p < 0.01) with a lower proportion of females (37.4% vs. 45.1%; p = 0.01) than those from Darlington. Although the CHA2DS2-VASc score was lower in AF patients in Fushimi than those in Darlington (5.18 vs. 5.57; p < 0.01), oral anticoagulation (OAC) was prescribed significantly more frequently in Fushimi (68.3%) than Darlington (61.7%) (p = 0.02). Multivariate logistic regression analysis showed that Japanese ethnicity was associated with a significantly decreased risk of recurrent stroke (OR 0.59. 95% CI 0.36–0.97; p = 0.04) but a significantly increased risk of all-cause mortality (OR 1.76, 95% CI 1.18–2.66; p < 0.01) in AF patients with previous stroke. Conclusions: AF patients with previous stroke in the UK were at higher risk of recurrent stroke compared to Japanese patients, but OAC was utilised less frequently. There was a lower risk of recurrent stroke in the secondary prevention cohort from the Fushimi registry, but an increased risk of all-cause mortality.